Effects of L-arginine on gut microbiota and muscle metabolism in fattening pigs based on omics analysis - Liu, Chengming; Yang, Yiting; Wang, Meng; Jiang, Wenyu; Du, Yong; Hao, Ziling; Chen, Lei; Zhu, Kangping; Liu, Bin; Niu, Lili; Zhao, Ye; Wang, Yan; et al. (Frontiers in Microbiology, 2024)
IntroductionL-arginine is an α-amino acid and a semi-essential nutrient of significant biological interest. It plays a role in influencing various aspects of animal meat traits, gut microbiota composition, and physiological metabolism.MethodsThis study aimed to investigate the combined effects of L-arginine supplementation on gut microbiota composition and the metabolism of the longissimus dorsi muscle in fattening pigs. Eighteen Yorkshire commercial pigs were divided into two groups: a control group that received no supplements and a treatment group that was given 1% L-arginine for 52  days. The diversity and composition of microorganisms in the feces of the control (NC) and L-arginine (Arg) groups were analyzed by sequencing the 16S rRNA V3 -V4 region of the bacterial genome.ResultsThe findings indicated that L-arginine supplementation increased both the abundance and diversity of gut microbiota, particularly affecting the Firmicutes and Bacteroidetes phyla. KEGG enrichment analysis revealed significant changes in several metabolism-related pathways, including amino acid, carbohydrate, and lipid metabolism. Metabolomic analysis identified 85 differential metabolites between the arginine and control groups, with phospholipids ranking among the top 20. Additionally, functional predictions indicated an increased abundance in the glycerophospholipid metabolism pathway. Correlation analysis linked changes in gut microbiota to phospholipid levels, which subsequently influenced post-slaughter meat color and drip loss.DiscussionThese results suggest that L-arginine supplementation positively impacts gut microbiota composition and the metabolic profile of the longissimus dorsi muscle in fattening pigs, with potential implications for meat quality.